KAJIAN MAKANAN VEGETARIAN KHAS BALI (Ragam, Proses Pengolahan, dan Nutrisi) - Ni Putu Eka Trisdayanti; AA. Gd. Putra KP. Dalem; Made Purwa Dana Atmaja (jurnal1, 2022)
Changing diet preference to vegetarian is certainly not easy. Most people are very dependent on the delicious taste of meat, so it is very difficult to switch to plant-based foods. In addition, tourists visiting Bali, especially vegetarians, will find it difficult to enjoy Balinese specialties, which are predominantly made from meat. With these issues in mind, and to suit the demands of both local communities and tourists, some vegetarian vendors in Bali started to offer vegetarian versions of traditional Balinese foods. The sample of Balinese traditional plant-based foods was analysed for their nutritional content. The data were analysed using the descriptive qualitative method. The Balinese traditional plant-based foods found in Ubud were Sate Lilit, Kuah Kare, Balinese soup, Sayur Urap, Betutu, Lawar, Tum, Dendeng/Ati, Sisit, Sate, and Urutan; which is made similar to Balinese food processing using Balinese spices (Base Genep) contains good nutrition.